K niektorým aspektom vzniku analytickej filozofie - Kvasz, Ladislav (Organon F, 2004)
The aim of the paper is to discuss some historical circumstaces of the constitution of analytic philosphy. The first of them is the birth of modern physics, which led to a new empirical attitude towards reality. The paper tries to underline the important role of scholastic philosophy together with the philosophy of Descartes in this process. The second part of the paper highlights some aspects of subjectivism, which played an important role in early modern philosophy. It shows the role of the desinterpretation of Descartes’ thoughts by the subjectivists. The overcoming of subjectivism by analytic philosophy can thus be viewed as a return to the same place, where Descartes originally stood.